Factor of Anxiety Level Primiparous Women - Fauziah Iinda Gurnita; Ari Suwondo; Rara Sri Endang PujiAstuti (Universitas Andalas, 2020)
The majority of primiparous woman signs of anxiety are often overlooked due to a lack of awareness of the impact of later life on the child's mother, husband or other family relationships which will be a psychological burden for primiparaous. Factors studied were age, education, job, economic status is not affected to anxiety level primiparous woman. Ethnic group influences anxiety level because it shapes the environment and effective perceptions for primiparous mothers and families. Because ethnic group make environmental entity shapes how the mother's psychological state runs during the postpartum process.